Biodiversity in the Anthropocene: prospects and policy - Seddon, N; Mace, G; Naeem, S; Tobias, J; Pigot, A; Cavanagh, R; Mouillot, D; Vause, J; Walpole, M (Royal Society, 2016)
Meeting the ever-increasing needs of the Earth’s human population without excessively reducing biological diversity is one of the greatest challenges facing humanity, suggesting that new approaches to biodiversity conservation are required. One idea rapidly gaining momentum—as well as opposition—is to incorporate the values of biodiversity into decision-making using economic methods. Here, we develop several lines of argument for how biodiversity might be valued, building on recent developments in natural science, economics and science-policy processes. Then we provide a synoptic guide to the papers in this special feature, summarizing recent research advances relevant to biodiversity valuation and management. Current evidence suggests that more biodiverse systems have greater stability and resilience, and that by maximizing key components of biodiversity we maximize an ecosystem’s long-term value. Moreover, many services and values arising from biodiversity are interdependent, and often poorly captured by standard economic models. We conclude that economic valuation approaches to biodiversity conservation should (i) account for interdependency and (ii) complement rather than replace traditional approaches. To identify possible solutions, we present a framework for understanding the foundational role of hard-to-quantify ‘biodiversity services’ in sustaining the value of ecosystems to humanity, and then use this framework to highlight new directions for pure and applied research. In most cases, clarifying the links between biodiversity and ecosystem services, and developing effective policy and practice for managing biodiversity, will require a genuinely interdisciplinary approach.